A Multimodal Discourse Analysis of Women’s Representation on Instagram: A Case Study of Chiara Ferragni - Ahmad , Fakhri; Ayendi, Ayendi (LingoLitera, 2026)
This research aims to analyze the construction of women’s identity through the multimodal representation in Chiara Ferragni’s Instagram post with the Multimodal Discourse Analysis approach by Kress & van Leeuwen (2006), together with supporting theories including Abidin's (2017) strategy of authenticity in influencer culture, Manovich's (2016) digital aesthetic, and Bourdieu's (1984) cultural capital. The data in the form of photos and captions were analyzed based on the visual aspect, including the composition, gaze, pose, lighting, color, filter, and the textual aspect, such as the caption, hashtags, mentions, and emojis. The findings of the study indicate that Ferragni’s identity was formed by the multifaceted multimodal strategy, where the visual elements typically highlight glamour, social status, and cultural legitimacy. Meanwhile, the caption is an element of textual reinforcement of the meaning via anchorage and appraisal metafunctions. The researcher establishes that the women's representation, specifically Chiara Ferragni, on Instagram was constructed by a planned multimodal construction, which displays women as modern figures with glamorous, authentic, and influential in digital culture.